The complete mitochondrial genome of Allonychiurus kimi (Lee, 1973) (Collembola: Onychiuridae). Issue 1 (2nd January 2021) - Lee, Yun-Sik; Lee, Taekjun; Kim, Philjae; Son, Jino; Wee, June; Kim, Yongeun; Hong, Jinsol; Lee, Minyoung; Cho, Kijong
Abstract: The complete mitochondrial genome of Allonychiurus kimi (Lee, 1973 ) was sequenced, assembled, and annotated. The mitochondrial genome of A. kimi is 14, 386 bp in length and contains 13 protein-coding, 22 transfer RNA, and 2 ribosomal RNA genes . A. kimi was closely clustered with the following species of the family Onychiuridae: Onychiurus orientalis, Orthonychiurus forlsomi, and Tetrodontophora bielanensis.